A Temperament-Attachment-Mentalization-Based (TAM) Theory of Personality and Its Disorders - Karterud, Sigmund W.; Kongerslev, Mickey T. (Frontiers in Psychology, 2019)
Abstract Theories of personality and personality disorders need, from time to time, to be revised and updated according to new empirical and conceptual developments. Such development has taken place in the realms of affective neuroscience, evolution and social cognition. In this article we outline a new personality theory which claims that phenomena we usually ascribe to the concept personality are best understood by postulating a web consisting of three major constituents: Temperament (mainly primary emotions), attachment and self-consciousness (mentalizing). We describe these constituents, their neurobiological underpinnings, the subjective experiences they evoke and their behavioral implications. We discuss the relevance of the espoused theory for the field of personality disorders with references to borderline, narcissistic and avoidant personality disorders as well as the DSM-5 Alternative Model. Implications for social psychology, psychotherapy and common-sense self-understanding are outlined. The theory aims to bridge previous contradictions between natural sciences and hermeneutics by its propositions of the evolution of self-consciousness.